Determining Factors of Linguo-cultural Properties of Polysemantic Humor - Kendjaeva, Zemfira Alimjanovna (The Lingua Spectrum, 2026)
This article is devoted to the analysis of national and cultural factors as systemic determinants that define the specifics of the formation and interpretation of polysemantic humor. It explores the idea that polysemantic linguistic units in a comic context become carriers of unique cultural codes, reflecting historical experience, value orientations, and the collective worldview of a specific community. English humor is based on lexical redundancy dating back to the Norman Conquest and the values of capitalism, utilizing the analytical structure of the language to create syntactic ambiguity. In turn, Russian humor is determined by the concept of fate, the tradition of "Aesopian language," and the experience of economic shortages, relying on rich morphology to express existential and reflexive meanings.